Analysis of Local Own-Source Revenue Components and Their Contribution to Regional Fiscal Independence: A Case Study of Tuban Regency - Kurniyati Indahsari (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
Tuban Regency should be able to achieve a “moderate” to “high” level of regional fiscal independence due to the dominance of its manufacturing industry sector. However, the data show that its fiscal independence level tends to be only “adequate” and even declined in 2022 and 2023. This study aims to analyze the performance of the components of own-source revenue (Pendapatan Asli Daerah/PAD) in Tuban Regency, which will then serve as a basis for formulating better PAD management policies in the future. The main data source is the development of PAD components in Tuban Regency during 2019–2023, which is analyzed using a descriptive quantitative approach. The analysis results indicate that the realization of PAD components fluctuates considerably, suggesting that the revenue structure is not yet strong and remains highly vulnerable to various factors that have not been fully controllable. To date, Tuban Regency’s PAD is still dominated by local taxes, largely contributed by the Non-Metal and Rock Minerals Tax (Mineral Bukan Logam dan Batuan/MBLB), a tax derived from the exploitation of natural resources that are difficult to renew. By its nature, this source is likely unsustainable in the long run. Therefore, it is necessary to strengthen the management of PAD components—particularly taxes and user charges/fees (retributions)—so that revenue from these sources can be better controlled. The novelty of this study lies in linking regional fiscal independence with the region’s economic structure. Meanwhile, its contribution is to provide empirical evidence on the urgency of increasing PAD from sources other than the utilization of natural resources—especially those that are difficult or non-renewable—to improve and sustain regional fiscal independence. Keywords: desentralisasi fiscal, kemandirian keuangan daerah, pendapatan asli daerah, pajak MBLB